Analysis of Vibration Characteristics of the Grading Belt in Wolfberry Sorting Machines - Yang Yu; Zhiwei Su; Junhao Zhang; Jinglong Li; Wu Qin (Applied Sciences)
The vibration of the belt drive system in fresh wolfberry sorting machines significantly impacts the sorting efficiency of wolfberries. To analyze the vibration changes induced by the belt drive, a simulation model was developed using multi-body dynamics software, Recur Dyn. The lateral vibration characteristics of the grading device’s belt were examined under varying initial tensions, speeds, and deflection angles. Response surface methodology (RSM) was employed to determine the relative influence of these factors on the belt’s vibration characteristics. The analysis indicated the order of influence, from greatest to least, as initial tension, deflection angle, and speed. Aiming to minimize the vibration amplitude at the belt’s midpoint, the optimal parameter combination was determined. The operating conditions yielding the minimum amplitude were found to be an initial tension of 520 N/mm, a drive speed of 60 rpm, and a belt deflection angle of 5°. Concurrently, a transverse vibration modal analysis was conducted to study the system’s natural frequencies and corresponding mode shapes, aiding in the identification of potential resonance issues. Finally, under optimal operating conditions, guided by the results of the belt simulation test, a 10 mm fillet was introduced at the edge of the pulley, effectively mitigating wear and vibration. Specifically, when the effective length of the transmission mechanism is set to 2200 mm and the total length of the fixed device is configured as 1600 mm, the amplitude attenuation rate achieves its peak value. This study demonstrates that the integration of theoretical analysis with simulation techniques provides a robust approach for optimizing the structural design of the grading device.